Middleware mechanisms for interaction interoperability in Collaborative Virtual Environments. (12th March 2010) - Ciampi, Mario; Gallo, Luigi; Coronato, Antonio; De Pietro, Giuseppe
In this paper, we discuss interaction interoperability in Collaborative Virtual Environments (CVEs), intended to mean the ability of two or more users to cooperate despite the heterogeneity of their interfaces. To allow such interoperability, rather than focusing on the decoupling of input devices from Interaction Techniques (ITs) and from interaction tasks, we suggest integrating interactive systems at higher level through an interface standardisation. To achieve this aim, we propose: i) an architectural model able to handle differences in input devices and interaction tasks; ii) an agent-based middleware that provides basic components to integrate heterogeneous user interfaces. We also present a prototype of an agent-based middleware able to support developers in the interconnection of monolithic applications and we introduce tools and languages we have used to formalise the interaction tasks considered in the case study.